Annotation of differential protein expression in the hypothalami of layer-type Taiwan country chickens in response to acute heat stress. (October 2018) - Tu, Wei-Lin; Cheng, Chuen-Yu; Chen, Chao-Jung; Chan, Hong-Lin; Wang, Shih-Han; Tang, Pin-Chi; Chen, Chih-Feng; Lee, Yen-Pai; Chen, Shuen-Ei; Huang, San-Yuan
Abstract: The hypothalamus is the coordinating center for maintaining temperature homeostasis. In this study, global protein expression in the hypothalami of layer-type Taiwan country chickens in response to acute heat stress was investigated. Twelve 30-week-old female TCCs were divided into three acute heat-stressed groups, namely acute heat stress at 36 °C for 4 h with 0 h (without recovery, H4R0), 2 h (H4R2), or 6 h (H4R6) of recovery. A control group was maintained at 25 °C. Hypothalamus samples were collected at the end of each time point for proteomic analysis. The analysis results revealed that 134 protein spots representing 118 distinct proteins exhibited differential expressions after acute heat stress treatment. Results of gene ontology analysis showed that most of the differentially expressed proteins are involved in carbohydrate metabolism, cellular processes, actin cytoskeleton organization, and responses to stimuli. Functional pathway analysis results suggested that the proteins are associated with networks of carbon metabolism, glycolysis, and gluconeogenesis. Upregulation of the expression of triosephosphate isomerase, phosphoglycerate kinase, pyruvate kinase, alpha-enolase, glycogen phosphorylase (brain form), phosphoglucomutase, L-lactate dehydrogenase A chain and downregulation of 6-phosphogluconolactonase expression indicated an increase in the glycolytic activity and glucose supply for ATP production in the hypothalami in response to heat stress. By contrast, upregulated expressions of heat shock protein 90 alpha, glutathione S-transferase 2s, peroxiredoxin-1, and dihydropyrimidinase-like 2 suggested that acute heat stress adversely affects the hypothalamus; thus, it induces mechanisms that prevent oxidative damage and endoplasmic reticulum stress. In conclusion, acute heat stress induces differential protein expression in the hypothalami of the L2 strain Taiwan country chickens, which may manifest detrimental effects. Furthermore, differential expression is a critical response in the hypothalamus for the regulation of thermotolerance. Highlights: The change of hypothalamus proteins after acute heat stress was analyzed. Acute heat stress induced differential protein expression in chicken hypothalamus. A total of 118 proteins differed significantly after acute heat stress treatment. Differentially expressed proteins associated with carbon and energy metabolism.